2021
DOI: 10.1111/iej.13484
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of mitochondrial dynamics, inflammation and mineralization potential of lipopolysaccharide‐induced human dental pulp cells after exposure to N‐acetyl cysteine, Biodentine or ProRoot MTA

Abstract: Aim To investigate the effects of N‐acetyl cysteine (NAC), Biodentine, ProRoot MTA and their combinations, on cell viability, mitochondrial reactive oxygen species (mtROS) production, mineralization and on the expression of genes related to inflammatory cytokine production, mitochondrial dynamics and cell apoptosis of lipopolysaccharide (LPS)‐induced human dental pulp cells (hDPCs). Methodology Isolated hDPCs were exposed to 20 μg mL−1 of Escherichia coli (E. coli) LPS for 24 h, before the experiment, except f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…Teneligliptin also reduces expression of TLR4 [ 26 ]. Another study showed that hDPCs treated with NAC (N-acetylcysteine), combined with Biodentine or Mineral trioxide aggregate (MTA) (cement compounds used in pulpitis treatment) [ 27 ], showed better viability. The group with MTA and NAC treatment also promoted mineralization [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Teneligliptin also reduces expression of TLR4 [ 26 ]. Another study showed that hDPCs treated with NAC (N-acetylcysteine), combined with Biodentine or Mineral trioxide aggregate (MTA) (cement compounds used in pulpitis treatment) [ 27 ], showed better viability. The group with MTA and NAC treatment also promoted mineralization [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…There have been numerous studies on the in vitro biocompatibility and bioactivity of calcium silicate-based bioceramics in endodontics ( 16 , 79 , 147 , 192 ). MTA has been investigated most thoroughly and is considered the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…Increased Alp activity and dentin matrix protein expression levels have been observed in human DPSCs stimulated with Biodentine ( 75 - 78 ). Furthermore, Biodentine significantly increases calcium deposition ( 79 ) and enhances the production of Ocn and Runx2 in human DPSCs stimulated with lipopolysaccharide (LPS) although there is no change in ALP expression levels ( 53 ). In terms of the inflammatory response, Biodentine does not affect high expression of IL-6 and IL-8 in DPSCs induced by LPS stimulation but decreases levels of the anti-inflammatory cytokine TGF-β1 ( 53 ).…”
Section: Stem Cellsmentioning
confidence: 99%
“…Isolation of HDPCs was done according to the method described by Weekate and colleagues (Weekate et al, 2021). In brief, the harvested pulp tissues were digested using Collagenase I (Gibco/Invitrogen) and Dispase II (Sigma‐Aldrich) and cultured in α‐MEM (Sigma‐Aldrich) supplemented with 10% fetal bovine serum (Gibco/Invitrogen), 100 U/ml of penicillin and 100 μg/ml of streptomycin (Sigma‐Aldrich), and 100 μmol/L of L‐ascorbic acid (Sigma‐Aldrich) at 37°C with 95% air and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Each group was treated with either vehicle, 20 μg/ml LPS, 400 μM H 2 O 2 , and combined LPS and H 2 O 2 or the two combined, for 24 h. LPS (Ultra‐Pure LPS‐EB from Escherichia coli , 0111:B4 strain; #0000110081) were purchased from Sigma‐Aldrich. The 20 μg/ml LPS and 400 μM H 2 O 2 were used in this study because previous studies demonstrated that 20 μg/ml LPS (Weekate et al, 2021; Yang et al, 2019) and 400 μM H 2 O 2 (Kim et al, 2017; Lee et al, 2015) induced the pathological condition in HDPCs and osteoblasts. The details of each group are as follows: (1) vehicle group: cells were incubated in ⍺‐MEM for 24 h; (2) LPS group: cells were incubated in ⍺‐MEM containing LPS 20 μg/ml for 24 h; (3) H 2 O 2 group: cells were incubated in ⍺‐MEM containing 400 μM of H 2 O 2 for 24 h; and (4) the two combined group: cells were incubated in ⍺‐MEM containing 400 μM of H 2 O 2 and 20 μg/ml of LPS for 24 h. After 24 h, cells in each group were subdivided into three subgroups.…”
Section: Methodsmentioning
confidence: 99%